(untitled) (Research, Society and Development, 2026)
This exploratory study aimed to evaluate the physicochemical quality and labeling compliance of compounded creams containing Glycyrrhiza glabra L. extract, purchased from compounding pharmacies in Ourinhos, São Paulo. Two commercial samples were obtained and analyzed according to the Cosmetic Product Quality Control Guide and RDC No. 67/2007. The analyses included organoleptic assessment, pH determination, apparent density, centrifugation testing, and labeling verification. The results showed that both samples presented pH values consistent with dermatological products and densities within or close to the expected range for cosmetic emulsions. However, sensory differences were observed between the creams, and sample A displayed physical contamination by a thread fragment. In the centrifugation test, sample B demonstrated slight instability, evidenced by the formation of an oily film. Labeling analysis revealed partial compliance with RDC No. 67/2007, with the absence of the prescriber’s name on both samples and the lack of directions for use on sample A. In conclusion, although the formulations exhibited acceptable physicochemical parameters, they showed manipulation and labeling deficiencies that reinforce the need for stricter adherence to good practices in compounding pharmacies. Accelerated and microbiological stability studies are recommended to further assess the safety of these formulations.